Earthing Method Reducing the Length of Acute Respiratory Infection Among Preterm Infants - Estiningtyas Estiningtyas; Anindhita Yudha Cahyaningtyas; Muhammad Akhsin Muflikhun (State Islamic University of Sunan Ampel, 2022)
Preterm infants have compromised immune systems where the maturity of the organs and body system is not optimum. The compromised immune system makes premature infants susceptible to micro-bacterial infections. Acute respiratory infection is the most common infection among them. This study aimed to investigate the significant difference in the length of acute respiratory infection before and after Earthing therapy. This research is a quasi-experimental study. The location is Sukoharjo District, Indonesia, from March to August 2021. The population in this study is preterm infants whose data is obtained from monthly reports on Central Java Statistic Agency. The number of samples of preterm infants was 192 infants. The sample size was 20 infants. Earthing duration is 1 hour every day for 30 days. The statistical analysis results in a P-value of 0,000 and t-count 8.065>t table 2.093, indicating a significant difference in the length of Acute Respiratory Infections among preterm infants before and after Earthing therapy. It is recommended that mothers of preterm infants continue to utilize Earthing devices longer to increase the immune system and prevent acute respiratory infection. Furthermore, using Earthing therapy is beneficial for improving the general immune system in preventing or accelerating the healing process of microbial infection with Earthing devices or straight to the ground.